2023
DOI: 10.1002/adfm.202300856
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Cilia–Bridging the Gap with Nature

Abstract: Human ingenuity has found a multitude of ways to manipulate fluids across different applications. However, the fundamentals of fluid propulsion change when moving from the macro‐ to the microscale. Viscous forces dominate inertial forces rendering successful methods at the macroscale ineffective for microscale fluid propulsion. Nature however has found a solution; microscopic active organelles protruding from cells that feature intricate beating patterns: cilia. Cilia succeed in propelling fluids at small dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 142 publications
1
3
0
Order By: Relevance
“…We use the proximity value c l / δ to represent cilia spacing for better comparison with the literature. 36 Note that in earlier simulation studies, similar effects of cilia spacing on flow generation have been found using a different numerical framework. 41 Our current results experimentally demonstrate and numerically confirm these earlier studies that fluid flow can indeed be generated by reciprocal cilia subjected to metachronal waves.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…We use the proximity value c l / δ to represent cilia spacing for better comparison with the literature. 36 Note that in earlier simulation studies, similar effects of cilia spacing on flow generation have been found using a different numerical framework. 41 Our current results experimentally demonstrate and numerically confirm these earlier studies that fluid flow can indeed be generated by reciprocal cilia subjected to metachronal waves.…”
Section: Resultssupporting
confidence: 65%
“…2 Another, perhaps more fundamental issue with the current approaches, is that the spacing between the artificial cilia are about the same as their length, 28,29 while natural cilia are much more closely packed. 30,36 This is not coincidental: when the magnetic cilia are too close to each other, the dipole–dipole interactions between them will interfere with their motion, causing the formation of ciliary pairs or bundles, after which their motion can no longer be controlled. 4,26 This is not a trivial problem because interciliary spacing is critical to the mechanism of metachronal motion and reducing spacing can strongly increase fluid transport, as shown earlier by theoretical and numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Taking inspiration from nature, various studies have explored the development of artificial cilia to achieve active self-cleaning. 408,409 These synthetic cilia typically manifest as arrays of micro/nanoscale soft actuators, activated through diverse mechanisms such as magnetic fields, 398,410 light, 411 electric fields, 412 and pneumatic forces. 413 These artificial cilia are actuated to generate hydrodynamic and mechanical forces on water droplets or particles, overcoming the adhesion force with either the substrate or the cilia themselves, effectively achieving self-cleaning effects.…”
Section: Approaches To Durable Actuatorsmentioning
confidence: 99%
“…The efficient fluid transport by biological cilia has inspired the design of artificial biomimetic cilia for use in microfluidic applications [26][27][28][29][30][31][32] or to fabricate swimming microrobots [33,34]. In these examples, cilia are actuated by external (e.g.…”
Section: Introductionmentioning
confidence: 99%